ORGANIZATION OF THE FINANCIAL MONITORING AT THE ENTERPRISES OF THE TRANSPORT COMPLEX - M. Maltseva; V. Savchenko-Belskii (Вестник университета)
The indicators of financial stability of the transport company, the role of financial recovery in the system of crisis management of the organization have been considered. The essence, goals and objectives of financial recovery have been analyzed. Methodological approaches to assessing the solvency of transport enterprises as part of the analysis of their financial and production activities have been proposed. The features of the management of the transport organization in conditions of uncertainty and risk have been revealed. The main causes of insolvency of transport companies have been considered. The factors influencing the formation of the financial policy of the enterprises of the transport complex have been traced. The importance of assessing the long-term prospects for the development of the enterprise, analyzing its capabilities, and the influence of external factors has been emphasized. The stages of improving the system of financial monitoring by a transport organization have been highlighted.